Promoting Urban Planners for Sustainable Development: Responsive Education in Transforming City Regions - Bayro Kaiser, Fabio; Ostos-Prieto, F. Javier; Reicher, Christa (European Public & Social Innovation Review, 2025)
Introduction: Unprecedented urban growth poses social and environmental challenges that require integrated planning and interdisciplinary education. Universities, particularly postgraduate programmes such as Transforming City Regions, have a crucial role to play in addressing these challenges. Methodology: This study uses a combination of theoretical and practical analysis and questionnaires to examine the impact of the Transforming City Regions programme on the education of future urban planners. Findings: The paper finds that students wishing to pursue a career in urban planning have a multidisciplinary educational background, which provides them with appropriate characteristics for urban planning. Discussion: Although initially challenging, students improve their practical application of theoretical knowledge throughout the Master's programme. The emphasis on research skills and critical analysis is crucial for the development of new areas and sustainable cities. Conclusions: The paper concludes that university Master's programmes provide a robust education in urban planning, capable of addressing current issues, but requiring continuous review processes to enhance learning.